Association of CRP Level with The Outcome in Patients with Cerebrovasular Accidents: A Case-Control Study (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Cerbrovascular Accidents (CVA’s) are a major burden over the society with highly associated mortality as well as mortality. Therefore it is important to find the markers which may help us in order to determine its prognosis.Objective: To determine the mortality rate and frequency of poor outcome among patients presenting with CVA along with the relation to higher and normal CRP levels obtained within 24 hours of the start of symptomsMaterial and Methods: This case-control study was conducted at Neurology department of Sir Ganga Ram Hospital/ Fatima Jinnah Medical University, Lahore. Total duration of study was 18 months, from January, 2015 to June, 2016. All the patients with CVA presenting in Emergency department of the hospital within 24 hours of start of symptoms were included in the study. Patients underwent CT scan to confirm the diagnosis of CVA. Their blood sample of 3 ml quantity was obtained for CRP levels. According to CRP level, they were dichotomized into 2 groups: ≥6 mg/L (Cases); 2 and mortality respectively.Conclusion: We conclude that CRP level is an easily available test and if it is higher than normal in patients with CVA, it is associated with poor outcome and higher mortality. So we may use this test routinely in order to predict the morbidity of the disease.
Keywords: Cerbrovascular Accident; Ischemic stroke; intracerebral hemorrhage; C-reactive protein; Outcome